Edukasi Period After Opening (PAO) Skincare, Cantik Sehat dengan Produk Aman Pada Siswa/i SMPN 10 Samarinda - Candrakanti, Bratandari Hana; Lailatul Alivia; Aditya Fridayanti; Dathin Aulia Delarosa; Septiayu Dwi Hartienah; Nur Zakiyah Darajat (Universitas Mataram, 2025)
The use of skincare products among adolescents is increasing, yet it is often not accompanied by adequate knowledge regarding safety and proper usage. One important aspect that is frequently overlooked is the period after opening, which determines the safe duration of product use after the packaging is opened. This issue may lead to health risks such as irritation, infection, and reduced skin quality if products are used beyond the recommended period. This activity aimed to improve students’ understanding of the period after opening, its difference from the expiration date, and the importance of selecting safe and authorized products. The method included health education through counseling, distribution of fan-shaped leaflets, question-and-answer sessions, and interactive games, followed by pre-test and post-test assessments involving 38 students of SMP Negeri 10 Samarinda. The analysis showed an increase in the average knowledge score from 11.34 in the pre-test to 15.21 in the post-test, with a paired t-test result indicating a significance value of 0.000 (p < 0.05), demonstrating a significant difference before and after the education. The majority of students who initially had a moderate level of knowledge improved to a good category after the intervention. In conclusion, education on the period after opening and safe use of skincare products proved effective in enhancing students’ knowledge and critical awareness, thereby serving as a preventive effort to protect adolescent skin health.